Chayote—Sechium edule (Jacq.) Sw. - James M. Stephens (EDIS)
This document provides an overview of the chayote (Sechium edule), a perennial-rooted cucurbit native to Guatemala and popular in tropical regions. The chayote plant produces light green, pear-shaped fruits with a single edible seed. The article details the plant's description, cultivation practices, and uses, highlighting the need for trellises, proper planting techniques, and fertilization. Chayote fruits are versatile in culinary applications, including creaming, frying, baking, and pickling. Proper storage methods are also discussed to maintain the fruit's edibility post-harvest.